Circadian rhythms and sleep chronotypes and their genetic basis - Omelyanovich, Віталій (Psychosomatic Medicine and General Practice, 2024)
Introduction. Circadian rhythms are cyclical changes in cellular, molecular, and biological processes that repeat approximately every 24 hours. Driven by an internal “biological clock” that is largely anatomically located in the suprachiasmatic nucleus and influenced by environmental stimuli, circadian rhythms play a central role in regulating many aspects of physiological processes, including sleep-wake cycles. Sleep chronotype, sometimes referred to in the literature as circadian preference, is part of circadian rhythmicity and is usually defined as individual variation in the preferred timing of the sleep-wake cycle. Interest in the genetic basis of circadian rhythmicity has been around for a long time. To date, great strides have been made in identifying a number of molecules that constitute the basic circadian biological clock that functions in every cell, not just in the suprachiasmatic nucleus of the cerebrum. Methods. Our study aimed to investigate the current state of scientific knowledge on the genetic basis of circadian rhythms, sleep chronotypes, their features of functioning and disorders, including hereditary sleep pathology. Materials. The study material is data from publications of research results on the genetic basis of sleep chronotypes, circadian rhythms and the functioning of the "biological clock", presented in peer-reviewed scientific publications of the last twenty years. Results. The interaction between circadian rhythms and sleep homeostasis was first summarized in the “two-process model.” It offers a description of sleep regulation that relies on both the circadian system (process C) and sleep homeostasis (process S). Process C depends on an approximately 24-hour rhythmic change in sleep propensity balanced by process S, which increases as a function of wakefulness. To date, great progress has been made in identifying a number of molecules that constitute the basic circadian biological clock, which functions in every cell and not exclusively in the suprachiasmatic nucleus (SCN). Based on scientific studies in model systems, it is now clear that the molecular circadian clock consists of a negative feedback loop involving the PER genes (PER1, PER2, and PER3) and CRY (CRY1 and CRY2), although other genes also play a significant role. As PER and CRY proteins accumulate in the cytoplasm of cells during the subjective “day,” both heterodimers repress BMAL1-CLOCK-mediated transcription and ultimately repress their own transcription (i.e., PER and CRY). This inhibition is relieved by the degradation of these proteins by targeting them for degradation by ubiquitin. Conclusions. Although the results of genetic studies are not always unambiguous, general patterns suggest that multiple genes play important roles in influencing circadian typology. At present, the presence of a connection between polymorphisms of biological clock genes that affect the circadian oscillator and sleep chronotype is clear, but the complete neurophysiological and molecular mechanisms of individual differences in chronotypes are unknown, although hypothetically they may also be associated with biological clock genes.